L’apport des expressions idiomatiques à la compréhension interculturelle. Cas des étudiants de L3 spécialisés en FLE - Souad Benabbes (Multilinguales)
The confinement imposed by the State since April 2020 on the Algerian university obliged us to sometimes resort to video to evaluate the oral skills. The proposed activity required 3rd year undergraduate students to make a 4 minute video in which they presented some French and Algerian idioms by first presenting the expression in its original language, then to translate it into French / in Arabic and describe in what context the expression is used. This contribution therefore seeks to analyze the effect of the use of idioms on the development of intercultural understanding among these students and to examine the relationship to oneself and the relationship to others. More specifically, we try to answer the following questions : what are the difficulties encountered by students when switching back and forth between Algerian Arabic and French ? How do these students manage to appropriate the culture of the Other through these expressions ?